2021
DOI: 10.1371/journal.pone.0250988
|View full text |Cite
|
Sign up to set email alerts
|

Missed opportunity for family planning counselling along the continuum of care in Arusha region, Tanzania

Abstract: Introduction Adequate sexual and reproductive health information is vital to women of reproductive age (WRA) 15 to 49 years, for making informed choices on their reproductive health including family planning (FP). However, many women who interact with the health system continue to miss out this vital service. The study aimed to identify the extent of provision of FP counselling at service delivery points and associated behavioral factors among women of reproductive age in two districts of Arusha region. It als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…35 Similar findings were observed in other countries. 36,37 Our study showed 49 percent of women received counseling on all important aspects of the postnatal period, which is similar to other studies. 38,39 The continuum of maternal care pathway that connects three components of care that is, ANC, skilled birth attendants, and PNC is a vital approach for addressing maternal, newborn, and child health challenges.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…35 Similar findings were observed in other countries. 36,37 Our study showed 49 percent of women received counseling on all important aspects of the postnatal period, which is similar to other studies. 38,39 The continuum of maternal care pathway that connects three components of care that is, ANC, skilled birth attendants, and PNC is a vital approach for addressing maternal, newborn, and child health challenges.…”
Section: Discussionsupporting
confidence: 90%
“…35 Similar findings were observed in other countries. 36,37 Our study showed 49 percent of women received counseling on all important aspects of the postnatal period, which is similar to other studies. 38,39…”
Section: Discussionsupporting
confidence: 89%
“…This was supported by previous studies. 16 21 22 This was inconsistent with some previous studies from Ethiopia, which indicated a lack of association between family planning counselling and postpartum modern contraceptive uptake. 23 26 27 One reason for the inconsistency might be due to the differences in the quality of the family planning counselling.…”
Section: Discussionmentioning
confidence: 81%
“…[13][14][15] Provision of family planning counselling during pregnancy, childbirth and postpartum periods is one of the key strategies to improve postpartum modern contraceptive uptake and space subsequent pregnancies. 16 Furthermore, increasing pregnancy spacing could prevent up to 32% of maternal and 21% of child mortalities. 1 In order to improve postpartum contraceptive uptake in low/middle-income countries, the WHO recommends that women receive family planning counselling integrated within maternal and child health services, such as antenatal care (ANC), childbirth, postnatal care (PNC), and well-baby care, immunisation and growth monitoring.…”
Section: Open Accessmentioning
confidence: 99%
“…As well as the quality of family planning counselling, evidence shows that the routine integration of quality FP counselling into the delivery of other health services, such as ANC/PNC visits and HIV testing, can lead to an increased uptake of family planning, and therefore a reduction in unmet need (Amour et al, 2021 ; Dev et al, 2019 ). However, integration needs to be done in such a way as to ensure the quality of the family planning counselling is maintained.…”
Section: Barriers To Service Uptake That Contribute To Unmet Needmentioning
confidence: 99%